Words to like by - "Easwaran, Eknath" (Mumbai, 2006)
Words to Live By presents a daily affirmation drawn from the insights of history's most brilliant philosophers and poets. Framed by the simple wisdom of Eknath Easwaran, each message offers inspiration and practical guidance for meeting life's challenges one day at a time. This lovely bedside companion can be consulted in the morning, as a touchstone for the day's events, or in the evening, as a way to quiet the mind.
Keywords: Thoughts